Peningkatan Prestasi Mahasiswa Pengulang Matakuliah Algoritma dan Pemrograman Melalui Peningkatan Motivasi Intrinsik dan Ekstrinsik - Budi Hartanto (Universitas Ciputra Surabaya, 2015)
Algorithm and Programming (Alpro) is the first programming course for the students in the Informatics Engineering department of the University of Surabaya (Ubaya). Unfortunately the failure rate for this course is still high. In the Second Semester, all students that take Alpro are the ones that must retake the course. In general the students that retake Alpro have a low learning spirit and self confidence. The content of the course and the possibility to achieve the highest grade are no longer attractive to them. In this condition it is necessary to find a different teaching approach that is different from the one that is used for regular class. The teaching approach that was applied in the Second Semester of academic year 2014/2015 is to strengthen the intrinsic and extrinsic motivation of the students in general. In addition, there was also a role playing that was applied to some students that joined it voluntarily. As a result of the approaches, the failure rate of the students that retake the Alpro decreased significantly from 40% in the Second semester of academic year 2013/2014 to just 14.8% in the Second semester of academic year 2014/2015. In addition, a stronger intrinsic and extrinsic motivation of the students that joined the role playing make them to have a good performance. The average final mark for the students that join the role playing is 81.7. This final mark is higher than the average final mark for the students that did not join the role playing, that is 70.56. This research shows a positive contribution of the intrinsic and extrinsic motivation to the students’ performance. The failure rate of the course can be decreased if the teacher can increase the students’ intrinsic and and extrinsic motivation. Some general strategies to increase the intrinsic and extrinsic motivation are presented in this paper, as well as a specific strategy in the form of a role playing. The success approach that is performed to decrease the failure rate of the students that retake Alpro can be developed to become a general approach by applying the approach to other courses or to the same course in the other University.